Leksikon dalam Pertunjukan Wayang Kulit Gagrag Surakarta: Kajian Etnolinguistik - Puspitasari, Niken Dwi; Solehah, Diya Ayu; Kristiyani, Marcella Wahyu; Nosita, Rohmah Tri; Novianto, Muhammad Akhbar; Nugroho, Miftah (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2025)
Gagrag shadow puppet performances are very popular in the Surakarta region. This study aims to describe the lexical and cultural meanings found in Surakarta gagrag shadow puppet performances. This is a descriptive qualitative study with an anthropological linguistic approach. The research data consists of the lexicon in Surakarta gagrag shadow puppet performances, which contains lexical and cultural meanings. In collecting data, this study uses non-participatory observation and literature review methods. Advanced recording techniques are used to transcribe and classify the data obtained. Primary data sources come from two informants who are experienced puppeteers, and secondary data sources come from supporting documents in the form of books containing information related to the subject matter. Based on the results of data analysis, this study shows that the lexicon in Surakarta-style shadow puppet performances is divided into three categories, namely people, elements, and equipment in shadow puppet performances. All data found were analyzed by describing them based on the lexical and cultural meanings obtained from informants and with the help of literature studies. Abstrak Pertunjukan wayang kulit gagrag sangat populer di wilayah Surakarta. Penelitian ini bertujuan untuk mendeskripsikan makna leksikal dan makna kultural yang ada dalam pertunjukan wayang kulit gagrag Surakarta. Jenis penelitian ini adalah kualitatif deskriptif dengan pendekatan linguistik antropologis. Data penelitian ini adalah leksikon dalam pertunjukan wayang kulit gagrag Surakarta yang mengandung makna leksikal dan kultural. Pada pengumpulan data, penelitian ini menggunakan metode observasi non-partisipasi dan studi kepustakaan. Teknik rekam dengan teknik lanjutan catat dipakai untuk mentranskrip dan mengklasifikasikan data yang sudah didapatkan. Sumber data primer berasal dari dua informan yang berpengalaman sebagai dalang dan sumber data sekunder berasal dari dokumen pendukung berupa buku yang memuat informasi mengenai materi terkait. Berdasarkan hasil analisis data, penelitian ini menunjukkan bahwa leksikon dalam pertunjukan wayang kulit gagrag Surakarta terbagi menjadi tiga kategori, yaitu orang, unsur, dan peralatan dalam pertunjukan wayang kulit. Keseluruhan data yang ditemukan dianalisis dengan mendeskripsikan berdasarkan makna leksikal dan makna kultural yang didapatkan dari informan serta bantuan studi kepustakaan.